The Benefits of Learning Analytics for Education: An Analysis of the Experiences of Lithuanian General Education School Teachers - Melnikova, Julija; Batuchina, Aleksandra; Šakytė-Statnickė , Gita; Šmitienė, Gražina (Acta Paedagogica Vilnensia, 2022)
The article discusses the benefits of learning analytics for education: the theoretical part reveals the concept of learning analytics, discusses how learning analytics technologies help to improve the teaching / learning process. The focus is on the most important group of learning analytics beneficiaries - teachers. The benefits of learning analytics in teachers’ pedagogical work are discussed. The empirical part of the article presents the results of a qualitative study for the analysis of teachers’ experiences. The study involved 17 teachers from Lithuanian general education schools with experience in working with learning analytics tools. The semi-structured interview method allowed to gather the research participants’ insights into the use of learning analytics in Lithuanian schools from the perspective of teachers. Qualitative analysis of the content of the informants’ answers revealed teachers’ opinion on the benefits of learning analytics for teaching and learning, teachers’ competencies to work with learning analytics tools, empowering teachers to use learning analytics tools and to make data-based pedagogical decisions.